2021
DOI: 10.1007/s40820-021-00598-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplatforms for Sepsis Management: Rapid Detection/Warning, Pathogen Elimination and Restoring Immune Homeostasis

Abstract: Sepsis, a highly life-threatening organ dysfunction caused by uncontrollable immune responses to infection, is a leading contributor to mortality in intensive care units. Sepsis-related deaths have been reported to account for 19.7% of all global deaths. However, no effective and specific therapeutic for clinical sepsis management is available due to the complex pathogenesis. Concurrently eliminating infections and restoring immune homeostasis are regarded as the core strategies to manage sepsis. Sophisticated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 271 publications
(229 reference statements)
0
13
0
Order By: Relevance
“…The synergistic scavenging resulted in a better anti-inflammatory effect, which also reflected the advantage of materials with the ability to scavenge multiple inflammatory mediators. Overexpression of NO by inducible nitric oxide synthase (iNOS) contributed to excessive inflammation in sepsis . We also illustrated the anti-inflammatory ability of TMPP by changes in NO content at the cellular level, where the content of NO in the cell culture while supernatant increased significantly after LPS stimulation, but NO production was significantly inhibited by the addition of TMPP (Figure S14B).…”
Section: Resultsmentioning
confidence: 87%
“…The synergistic scavenging resulted in a better anti-inflammatory effect, which also reflected the advantage of materials with the ability to scavenge multiple inflammatory mediators. Overexpression of NO by inducible nitric oxide synthase (iNOS) contributed to excessive inflammation in sepsis . We also illustrated the anti-inflammatory ability of TMPP by changes in NO content at the cellular level, where the content of NO in the cell culture while supernatant increased significantly after LPS stimulation, but NO production was significantly inhibited by the addition of TMPP (Figure S14B).…”
Section: Resultsmentioning
confidence: 87%
“…Most studies have focused on the exosome-mediated transport of micro-RNAs and proteins. [15,16] Further, current research has focused on the functions of "natural" exosomes, such as those secreted by adipose tissue-derived stem cells, which can reduce vascular leakage and improve organ function by regulating the Nrf2/HO-1 axis to polarize macrophages into anti-inflammatory phenotypes, thus suppressing sepsis-associated inflammation and organ damage. [17] Exogenous endothelial progenitor cell derived exosomes offer protection against sepsis by reducing vascular leakage and improving organ function.…”
Section: Discussionmentioning
confidence: 99%
“…In previous genomic and transcriptomic studies, many studies have focused on the differences between septic patients and healthy individuals [ 3 ], but there are insufficient studies on the mechanism of action of septic shock. Studies have shown that early warning and identification of risk factors for patients with sepsis can lead to faster and more accurate standardized treatment, which is helpful for the diagnosis, treatment and prognosis of sepsis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%